High phenotypic variation found within the offspring of each mother tree in Fagus sylvatica regardless of the environment or source population - Jonas Schmeddes; Lena Muffler; Adrià Barbeta; Ilka Beil; Andreas Bolte; Stefanie Holm; Pascal Karitter; Marcin Klisz; Magnus Löf; Manuel Nicolas; Josep Peñuelas; Yann Vitasse; et al. (Global Ecology and Biogeography, 2024)
Aim Climate change challenges temperate forest trees by increasingly irregular precipitation and rising temperatures. Due to long generation cycles, trees cannot quickly adapt genetically. Hence, the persistence of tree populations in the face of ongoing climate change depends largely on phenotypic variation, that is the capability of a genotype to express variable phenotypes under different environmental conditions, known as plasticity. We aimed to quantify phenotypic variation of central Europe's naturally dominant forest tree across various intraspecific scales (individuals, mother trees (families), populations) to evaluate its potential to respond to changing climatic conditions. Location Europe. Time Period 2016–2019. Major Taxa Studied European beech ( Fagus sylvatica L.). Methods We conducted a fully reciprocal transplantation experiment with more than 9000 beech seeds from seven populations across a Europe‐wide gradient. We compared morphological (Specific Leaf Area), phenological (leaf unfolding) and fitness‐related (growth, survival) traits across various biological scales: within single mother trees, within populations and across different populations under the contrasting climates of the translocation sites. Results The experiment revealed significant phenotypic variation within the offspring of each mother tree, regardless of geographic origin. Initially, seedling height growth varied among mother trees and populations, likely due to maternal effects. However, the growth performance successively aligned after the first year. In summary, we observed a consistent growth response in different beech populations to diverse environments after initial maternal effects. Main Conclusions The study strikingly demonstrates the importance of considering intraspecific variation. Given the surprisingly broad spectrum of phenotypes each mother tree holds within its juvenile offspring, we conclude that Fagus sylvatica might have the potential for medium‐term population persistence in face of climate change, provided that this pattern persists into later life stages. Hence, we also suggest further investigating the inclusion of passive adaptation and natural dynamics in the adaptive management of forests.